Techsource Programme: Simply Supported Reinforced Concrete Beam Design By Microsoft Excel - Kesot, Mohd Jahaya; Nazri, Rabiatul Adawiyyah; Shamsul Amri, Puteri Azira; Mansor Mohamad Mansor, Nur Shahelly (Multidisciplinary Applied Research and Innovation, 2021)
This study was conducted to help students in the form of providing and calculating the problems regarding reinforced concrete beam in the simplest and easiest way. The main reason students face multitude kinds of problems while calculating reinforced beam manually is due to the complex calculation in order to obtain the output analysis. Hence, a program is created in order to solve this complex calculation. This project presents a design of reinforced concrete beam by Microsoft Excel Visual for Application (VBA), mainly focusing on the problems that arise se from a long calculation that is both time and energy-consuming. In other words, this project promotes automatic calculation as opposed to a more difficult one where it is done manually. By using VBA as the medium attraction, this project offers attractive displays and produce automated applications such as data entry worksheet that can be used to generate reports, in addition to the ability to print the said reports in a PDF form, which is arguably the most convenient form and is accepted worldwide as of current status. Users only need to place an input of the required data onto this program and a desired output will be displayed. Users can also revise the previously printed PDF reports as their revision in the future. This report will act as a learning material for users as well as guidance in the design calculation process.